Lingua e nazione in Islanda - A. Meregalli (FrancoAngeli, 2012)
The aim of this essay is to analyse the function of the Icelandic language as identity factor within the Icelandic cultural system in a diachronic perspective. After describing the main characteristics and trends in the Icelandic linguistic politics of our days, a distinction is made between the cultural tradition from the Age of Settlement to the 18th century and the following period, when this heritage develops into aware linguistic purism in the framework of nationalistic self-definition and self-assertion.